ORGANIZATION AND CONTENT OF PROFESSIONAL AND PRACTICAL PHYSICAL TRAINING OF STUDENTS OF PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS - Uraimov Sanjar Ruzmatovich; Qodirova Shahlo Shavkatjon qizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article analyzes the theoretical knowledge of students studying at Fergana State University on physical development and professional-practical physical training.